2010
DOI: 10.1007/s11695-010-0129-8
|View full text |Cite
|
Sign up to set email alerts
|

The Decrease of Serum Levels of Human Neutrophil Alpha-Defensins Parallels with the Surgery-Induced Amelioration of NASH in Obesity

Abstract: Changes in levels of HNDs and sCD14 accompany those in hepatic necro-inflammation due to surgical-induced weight loss. Further studies are needed to verify any causative role of these peptides in non-alcoholic steatohepatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…We found that the mRNA levels of two antimicrobial peptides, cathelicidin antimicrobial peptide ( CAMP ) and alpha defensin 1/3 ( DEFA1/DEFA3 ), were significantly decreased after bariatric surgery. In two prior studies, plasma levels of alpha defensins were found to be decreased by 55 to 60% in women after bariatric surgery, and their levels were correlated with changes in plasma triglyceride levels and pathology based measures of liver steatosis and inflammation [23], [24]. Thus, our finding of decreased DEFA1/DEFA3 mRNA levels after bariatric surgery agrees with prior findings from plasma protein level measurement assays.…”
Section: Discussionsupporting
confidence: 90%
“…We found that the mRNA levels of two antimicrobial peptides, cathelicidin antimicrobial peptide ( CAMP ) and alpha defensin 1/3 ( DEFA1/DEFA3 ), were significantly decreased after bariatric surgery. In two prior studies, plasma levels of alpha defensins were found to be decreased by 55 to 60% in women after bariatric surgery, and their levels were correlated with changes in plasma triglyceride levels and pathology based measures of liver steatosis and inflammation [23], [24]. Thus, our finding of decreased DEFA1/DEFA3 mRNA levels after bariatric surgery agrees with prior findings from plasma protein level measurement assays.…”
Section: Discussionsupporting
confidence: 90%
“…This association may be envisioned as an attempt to buffer metabolic endotoxemia with increased fat mass. However, increased metabolic endotoxemia possibly results in increased turnover of sCD14 because weight loss results in both decreased LPS (J.M.M.-N. and J.M.F.-R. unpublished results) and increased sCD14 levels (29). …”
Section: Discussionmentioning
confidence: 99%
“…sCD14 is involved in innate immunity and its expression is increased by the presence of LPS and fatty acids that resemble the lipid portion of LPS. 34 It was also noted that mothers of children who were normal weight at age 10 y had statistically significantly higher mean concentrations of adiponectin in maternal colostrum than mothers of overweight children. Adiponectin is a protein hormone secreted from adipose tissue 35 and the placenta 36 into the blood stream.…”
Section: Other Technologies Employed To Investigate Microbial Ecosystemsmentioning
confidence: 97%